Conceptual framework of remote working in Serbia: towards gender differences - Stefan Sretenović; Marko Slavković; Vesna Stojanović-Aleksić (Anali Ekonomskog fakulteta u Subotici, 2022)
With the outbreak of the pandemic caused by the virus COVID-19, companies all around the world were affected and faced a new reality. In such circumstances, remote working was a necessary organizational response to the forthcoming crisis, to provide business continuity and protect their employees. For many companies, remote working is a completely new experience without any preparation period. The subject of the research is to reveal the perception and correlation between different variables, which are crucial for successful remote working implementation, within two groups of remote workers, male and female. This research highlights the differences and provides guidelines for successful remote working implementation for different genders. An original empirical research was conducted on a sample of companies that are doing business activities in Serbia and were deployed remote working for their employees during the COVID-19 pandemic to analyze the differences between male and female respondents toward five defined variables important for remote working: social support (SP), autonomy (A), monitoring (M), job performance (JP) and work engagement (WE) during remote working. The relationships between the indicated variables were tested by correlation analysis of 121 collected surveys.